Induction of human cytochrome P450 3A4 by the irreversible myeloperoxidase inactivator PF-06282999 is mediated by the pregnane X receptor. (3rd July 2018) - Moscovitz, Jamie E.; Lin, Zhiwu; Johnson, Nathaniel; Tu, Meihua; Goosen, Theunis C.; Weng, Yan; Kalgutkar, Amit S.
Abstract: 1. 2-(6-(5-Chloro-2-methoxyphenyl)-4-oxo-2-thioxo-3, 4-dihydropyrimidin-1(2 H )-yl) acetamide (PF-06282999) is a member of the thiouracil class of irreversible inactivators of human myeloperoxidase enzyme and a candidate for the treatment of cardiovascular disease. PF-06282999 is an inducer of CYP3A4 mRNA and midazolam-1′-hydroxylase activity in human hepatocytes, which is consistent with PF-06282999-dose dependent decreases in mean maximal plasma concentrations ( C max ) and area under the plasma concentration time curve (AUC) of midazolam in humans following 14-day treatment with PF-06282999. 2. In the present study, the biochemical mechanism(s) of CYP3A4 induction by PF-06282999 was studied. Incubations in reporter cells indicated that PF-06282999 selectively activated human pregnane X receptor (PXR). Treatment of human HepaRG cells with PF-06282999 led to ∼14-fold induction in CYP3A4 mRNA and 5-fold increase in midazolam-1′-hydroxylase activity, which was nullified in PXR-knock out HepaRG cells. TaqMan® gene expression analysis of human hepatocytes treated with PF-06282999 and the prototypical PXR agonist rifampin demonstrated increases in mRNA for CYP3A4 and related CYPs that are regulated by PXR. 3. Docking studies using a published human PXR crystal structure provided insights into the molecular basis for PXR activation by PF-06282999. Implementation of PXR transactivation assays in a follow-on discovery campaign should aid in the identification of back-up compounds devoid of PXR activation and CYP3A4 induction liability.